Study of carbohydrates in the leaves of the Poltava variety of Common lilac - Popyk , Andrii; Kyslychenko , Viktoriia; Novosel , Olena; Iosypenko , Olena (Annals of Mechnikov's Institute, 2025)
Introduction. Carbohydrates are the most common natural compounds in the plant world and have a wide range of medicinal properties. Due to their chemical structure, carbohydrates are capable of adsorbing radionuclides and heavy metals, improving lipid metabolism, activate the secretory and motor functions of the intestine, regulate the functions of the immune and endocrine systems, and exhibit emollient, anti-inflammatory, anticoagulant, antiulcer, antitumour, and antiviral effects. The advantage of carbohydrates is their low toxicity and antigenic and pyrogenic properties, which has led to their use in medical practice. That is why the search for new plant sources of carbohydrates is of great importance for modern medicine. One of the promising plant sources of carbohydrates may be common lilac, which grows widely in Ukraine. In traditional medicine in many countries, the leaves, flowers, fruits, buds and bark of the plant are used to treat malaria, rheumatoid arthritis, gout, headaches and to boost immunity. Experimental studies confirm the anti-inflammatory, immunomodulatory, antioxidant, antipyretic, antitumour and antiallergic properties of raw materials from plants of the Syringa genus. The aim of the study was to fractionally isolate, determine the qualitative composition and quantitative content of carbohydrates in the leaves of the common lilac of the Poltava variety. Materials and methods. The object of the study was the leaves of the common lilac of the Poltava variety, harvested in the botanical garden (Kharkiv) in May 2025. Carbohydrates were identified using paper chromatography in comparison with standard sugar samples and high-performance liquid chromatography. The quantitative content of polysaccharides and polysaccharide fractions in the leaves of common lilac was determined by the gravimetric method. Results and discussion. As a result of studying the carbohydrate composition of leaves of the common lilac of the Poltava variety using paper and high-performance liquid chromatography, the presence of glucose, fructose, a mixture of maltose and sucrose was established. Among the identified sugars, fructose prevailed in terms of quantitative content – 0.35±0.02 mg/ml. The content of water-soluble polysaccharides, determined by the gravimetric method, in the leaves of the common lilac of the Poltava variety was 9.35±0.27 %. Fractionation of polysaccharides in the leaves of the common lilac of the Poltava variety indicates a significant concentration of pectin substances. Conclusions. Using paper and high-performance liquid chromatography methods, the quantitative content of carbohydrates – glucose, fructose, a mixture of sucrose and maltose – was identified and determined in the leaves of the common lilac variety Poltava. Among the identified sugars in the leaves of the common lilac of the Poltava variety, fructose dominated in terms of quantitative content – 0.35±0.02 mg/ml. The polysaccharides in the leaves of the common lilac of the Poltava variety were fractionated and the quantitative content of the isolated fractions was determined, among which the fraction of pectin substances predominated in terms of content. The studies conducted indicate the promise of further in-depth study of the carbohydrates in the leaves of the common lilac of the Poltava variety, and the results obtained can be used to standardize the raw materials studied.